TYPES OF VIRTUAL REALITY TOOLS AND PLATFORMS USED IN LANGUAGE LEARNING - Nurullayeva Aziza G’ulomovna (The latest pedagogical and psychological innovations in education, 2025)
Virtual Reality (VR) has emerged as a transformative technology in language education, offering immersive, interactive, and contextualized learning experiences that surpass what traditional environments provide. This article reviews major types of VR tools used in language learning, including immersive VR headsets, desktop VR, 360-degree videos, social VR platforms, mobile VR, and AI-driven VR tools. Drawing on empirical literature and reflective commentary, the paper examines how these VR modalities influence vocabulary development, communicative competence, pronunciation, and intercultural learning. cognitive load, and teacher expertise.